'from education, from duty, and from principle': Irish Catholic loyalty in context, 1829-1874. Issue 3 (30th March 2017) - Keogh, Richard A.
Abstract : The passage of the Emancipation Act in 1829 presented an opportunity for Catholics to reimagine their loyalty as equal subjects for the first time under the union between Great Britain and Ireland. This article explores the way Catholic loyalty was conceived in the decades that followed the act of 1829 through to the mid 1870s, when there was renewed focus on the civil allegiance of Catholics following the declaration of Papal infallibility. Historians are increasingly exploring a range of social, political and religious identities in nineteenth century Ireland, beyond the rigid binary paradigm of Catholic nationalisms and Protestant loyalisms that has dominated Irish historiography. However, Catholic loyalty in particular remains an anachronism and lacks sufficient conceptual clarity. Our understanding of a specifically Catholic variant of loyalty and its public and associational expression, beyond a number of biographical studies of relatively unique individuals, remains limited. By providing an exposition of episodes in the history of Catholic loyalty in the early and mid-Victorian years this article illuminates the phenomenon. It demonstrates that Irish Catholic loyalty took on different expressive forms, which were dependent on the individuals proclaiming their loyalty, their relationship to the objects of their loyalty, and its reception by the British state and Protestant establishment.